Liver function tests in acute hepatitis in children - ., Shweta; Prasad, Rajiv Ranjan (International Journal of Research in Medical Sciences, 2017)
Background: Aim of study to analyse the elevation of liver enzymes of icteric children presenting as acute hepatitis and observe its association with hepatitis B surface antigen positivity rate. The liver function tests help us to monitor amount of hepatic dysfunction and early recognition and prediction of severity. This study was done to observe the degree of alteration in parameters of liver function test and predict the clinical outcome. Methods: Study was done in sixty-four children (upto age 12 years) presenting with symptoms of acute hepatitis in the paediatric OPD and emergency of Patna Medical College and Hospital, Patna. Fifty healthy children were taken as controls. Liver functions were evaluated under following parameters as serum bilirubin, SGPT, SGOT and ALP. Statistical analysis was done for significance. Results: The results showed higher HBsAg positivity in male children compared to females; also shows the pattern of enzyme elevation at first visit of the patient. Serum total bilirubin was raised (mean 3.94mg/dl ,SD was 0.62), the liver enzymes were also elevated with SGPT (mean 615.83IU/l, SD 98.2), SGOT (mean 562.86 IU/l, SD 110.18) and ALT( mean 330 IU/l, SD 115.82) levels. The rise was significant for SGOT and SGPT with hepatitis B surface antigen positivity rate, but levels of serum bilirubin and ALP remained non-significant. Conclusions: This study helps us to analyze the incidence of HBsAg positive cases presenting with clinical features of acute hepatitis and degree of alteration of liver functions would help the physician in better management of the cases.